2002
DOI: 10.1097/00004424-200201000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Media Increase Vascular Endothelial Permeability by Inhibiting Nitric-Oxide Production

Abstract: The present study suggested that contrast media increase vascular endothelial permeability by inhibiting NO production, leading to vascular endothelium-related adverse effects of contrast media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In another study, Furuta et al [34] showed that IXG and iohexol (a nonionic RC) reduced NO 2 − levels in human endothelial cell culture; this effect on NO was associated to an increased endothelial cell permeability, which was inhibited by sodium nitroprusside (SNP, an NO donor) and exacerbated by L-NMMA (N G -monomethyl-L-arginine, an NO inhibitor).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Furuta et al [34] showed that IXG and iohexol (a nonionic RC) reduced NO 2 − levels in human endothelial cell culture; this effect on NO was associated to an increased endothelial cell permeability, which was inhibited by sodium nitroprusside (SNP, an NO donor) and exacerbated by L-NMMA (N G -monomethyl-L-arginine, an NO inhibitor).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, additional factors, such as viscosity or some form of chemotoxicity, may play a role. Theories have included effects on vascular smooth muscle contractility (although there is ex vivo evidence that this is not the case (36)) and effects on vascular endothelial permeability secondary to inhibition of nitric oxide production (37).…”
Section: Osmolalitymentioning
confidence: 99%
“…This decrease was significantly attenuated by L-arginine, suggesting that NO plays a major role in the pathogenesis of radiocontrast-induced acute renal failure (21). One recent study suggested that contrast media increase vascular endothelial permeability by inhibiting NO production, with consequent vascular endothelium-related adverse effects (22).…”
Section: Discussionmentioning
confidence: 99%